A tale of two rare entities: extramammary Paget’s disease and hepatocellular carcinoma-a singular case report - Gupta, Sumedha; Kalwaniya, Dheer Singh; Zaheer, Sufiyan; Mourya, Pallavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
This case report underscores the intricate challenges in managing extramammary Paget’s disease (EMPD) of the vulva, a rare neoplasm with diverse clinical manifestations. The presented case, involving a postmenopausal woman, highlights the complexity of EMPD diagnosis and its association with underlying malignancies, particularly hepatocellular carcinoma (HCC). Despite initial management with 5% Imiquimod cream, the patient’s clinical course revealed the aggressive nature of the disease, as evidenced by the development of invasive HCC. The rapid deterioration and subsequent demise of the patient emphasize the need for comprehensive monitoring and early intervention in cases of EMPD, considering its potential association with internal malignancies. The discussion delves into the typical presentation of Paget’s disease, its association with adnexal carcinomas, and the challenging link between EMPD and internal malignancy. The retrospective analysis of cases in the literature further underscores the variability in underlying adnexal carcinoma rates, emphasizing the complexity of this association. In this particular case, immunohistochemical markers failed to establish a direct correlation between vulval EMPD and hepatocellular carcinoma, highlighting the need for continued research and understanding of the intricate pathogenesis of EMPD and its relationship with internal malignancies.